Return Of The Vampire - Geronimo Stilton
On a gloomy night of the full moon, a strange figure appears on the threshold of the Castle of the Skull: it is Camilo Dulceblood, an old adventure companion of Grandfather Ratonquenstein. He is a vampire, and his profession is to taste tomato juices. What is Camilo doing at the Tenebrax house at midnight?